Compositional and thermal analysis of RBD palm oil adulterated with lipase-catalyzed interesterified lard - Marikkar, J.M.N; Lai, O.M; Ghazali, H.M; Che Man, Y.B (Elsevier, 2002)
A study was conducted to determine the presence of enzymatically-randomized lard (ERLD) as an adulterant in RBD palm oil using three different analytical techniques, namely gas liquid chromatography (GLC), reversed phase high performance liquid chromatography (RP-HPLC) and differential scanning calorimetry (DSC). Lard extracted from the adipose tissues of pig was enzymatically interesterified using non-specific lipase from Pseudomonas sp. Compositional and thermal characteristics of ERLD were compared with those of genuine lard (GLD). RBD palm oil samples, adulterated separately with various levels of GLD and ERLD, were analyzed using GLC, HPLC and DSC. Neither GLC nor HPLC showed any characteristic adulteration peaks to enable RBD palm oil, adulterated with either GLD or ERLD, to be distinguished from those adulterated with chicken fat (CF). However, DSC provided a better means for identification of lard, with a detection limit of 1%.